PINOID AGC Kinases Are Necessary for Phytochrome-Mediated Enhancement of Hypocotyl Phototropism in Arabidopsis . Issue 3 (3rd October 2014) - Haga, Ken; Hayashi, Ken-ichiro; Sakai, Tatsuya
Abstract : Phytochrome-mediated phototropic enhancement depends on PINOID family kinases . Abstract: Several members of the AGCVIII kinase subfamily, which includes PINOID (PID), PID2, and WAVY ROOT GROWTH (WAG) proteins, have previously been shown to phosphorylate PIN-FORMED (PIN) auxin transporters and control the auxin flow in plants. PID has been proposed as a key component of the phototropin signaling pathway that induces phototropic responses, although the responses were not significantly impaired in the pid single and pid wag1 wag2 triple mutants. This raises questions about the functional roles of the PID family in phototropic responses. Here, we investigated hypocotyl phototropism in the pid pid2 wag1 wag2 quadruple mutant in detail to clarify the roles of the PID family in Arabidopsis ( Arabidopsis thaliana ). The pid quadruple mutants exhibited moderate responses in continuous light-induced phototropism with a decrease in growth rates of hypocotyls and normal responses in pulse-induced phototropism. However, they showed serious defects in enhancements of pulse-induced phototropic curvatures and lateral fluorescent auxin transport by red light pretreatment. Red light pretreatment significantly reduced the expression level of PID, and the constitutive expression of PID prevented pulse-induced phototropism, irrespective of red light pretreatment. This suggests that the PID family plays a significant role in phytochrome-mediated phototropic enhancement but not the phototropin signaling pathway. Red light treatment enhanced the intracellular accumulation of PIN proteins in response to the vesicle-trafficking inhibitor brefeldin A in addition to increasing their expression levels. Taken together, these results suggest that red light preirradiation enhances phototropic curvatures by up-regulation of PIN proteins, which are not being phosphorylated by the PID family.